GENDER IDENTITY FORMATION OF INDONESIAN WOMAN EFL TEACHERS: BECAUSE WOMB-MAN DOES EXIST - Asanti, Chris (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2016)
This study aims at investigating the gender identity formation of some Indonesian women EFL teachers as they had experiences in advancing their study abroad. The study adopted a qualitative methodology within a feminist framework. The data were generated from some women who had been teaching English in Indonesia for at least two years prior to coming to another country to further their education. Through self-completion questionnaires and focus group interviews, the participants shared their lived-experiences and their adjustments as they were exposed to different cultural movements transnationally, between Indonesia and another country. How these women EFL teachers construct their gender identity during their transnational movement and how English actually influences these processes is the focus of the study. The findings reveal how the processes of gender identity construction were formed through governmental policy and socio-cultural values in the society. The findings also show how for these women EFL teachers their professional milieu was a site of contestation for women to promote their status in the society and gender equality. Finally the study highlights that English language is viewed as a benefit to elevate women’s social status as it facilitated their socialization in professional and educational contexts when they furthered their study in another country. Drawing on the findings, further research is suggested around the issue of gender identity construction of men EFL teachers in order to get more comprehensive picture.Keywords: gender identity, women EFL teachers, English language